2008
DOI: 10.4049/jimmunol.180.1.530
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular HIV-Tat Induces Cyclooxygenase-2 in Glial Cells through Activation of Nuclear Factor of Activated T Cells

Abstract: Both the HIV-1 protein Tat and cyclooxygenase-2 (COX-2) have been involved in the neuropathogenesis associated with HIV-1 infection. However, the relationship among them has not been addressed. Here, we found that extracellular Tat was able to induce COX-2 mRNA and protein expression and PGE2 synthesis in astrocytoma cell lines and primary human astrocytes. Moreover, Tat induced COX-2 promoter transcription. Deletion of NF-κB sites of the promoter did not diminish Tat-dependent transcription. Interestingly, Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…HIV-1 increases COX-2 expression in the T lymphocytes and macrophages that it infects (20,21,23,25). The HIV-1 transcription factor Tat stimulates COX-2 transcription (44). HIV-1 infection can also increase plasma cytokines including IL-6 and TNFα (45, 46).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 increases COX-2 expression in the T lymphocytes and macrophages that it infects (20,21,23,25). The HIV-1 transcription factor Tat stimulates COX-2 transcription (44). HIV-1 infection can also increase plasma cytokines including IL-6 and TNFα (45, 46).…”
Section: Discussionmentioning
confidence: 99%
“…EMSA showed that PTH stimulated NFATc1 but not NFATc2–4 binding to a sequence spanning the composite site and that NFAT played a dominant role in the cooperative binding of NFAT and AP‐1 proteins to the composite site. Binding of NFAT and AP‐1 proteins to a composite NFAT / AP‐1 site is reported to be important in the regulation of expression of cytokine and surface receptor genes in immunocytes16, 46 and in the induction of COX‐2 by PMA and calcium ionophore in human T‐lymphocytes21 and by HIV‐Tat in glial cells 47. Our data indicate that this composite NFAT / AP‐1 element is also important for COX‐2 induction by PTH in osteoblasts and that constitutively active NFATc1 can enhance the basal and PTH‐stimulated expression of COX‐2 in osteoblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…As a target of MCP-1, Akt and Erk1/2 signaling proteins are indirectly affected by Tat. Additionally, reports suggest that Tat was able to induce COX-2 and PGE2 synthesis in astroglial cells through an NFAT/AP-1-dependent mechanism [58,59]. Another interesting finding demonstrates the importance of Tat cysteine-rich domain in regulating wnt/β-catenin signaling pathway.…”
Section: Reviewmentioning
confidence: 92%